Population status and habitat use of southern right whales in the sub-Antarctic Auckland Islands of New Zealand - J. Patenaude, Nathalie; Baker, C. Scott (J. Cetacean Res. Manage., 2020)
In the winters of 1995, 1996 and 1997, research was conducted in the Auckland Islands to evaluate the status of southern right whales in the New Zealand sub-Antarctic. Whales were present in high concentrations each year (maximum count of 146 whales) in a small area on the northeast side of the main island. Cow-calf pairs averaged 12% (range 9% to 14%) of the total population. Most cow-calf pairs were sighted resting at the surface (60%) or travelling (36%) and showed a strong preference for shallow ( < 20m depth) nearshore waters. The ratio of females to males, as determined by molecular sexing using biopsy samples, varied from 54% to 39% over the three years but did not differ significantly from 1:1 in any year. Both males and females were found in varying group sizes, with the occurrence of social/sexual activity predominant (85%) in groups of three or more whales. Most single whales were found resting (59%) and occasionally approached the research vessel (19%). A total of 217 individual whales have been photo-identified over the three years of this study, 24% of which were resighted more than once in a season and approximately 15% of which were resighted in more than one year. The high density of whales in Port Ross during winter months, the presence of cow-calf pairs, including newborns, and the frequency of social and sexual activity indicates that the Auckland Islands are a primary wintering habitat for southern right whales in New Zealand waters. However, the low resighting rates within season and documented movement to nearby Campbell Island (290km) suggest that some whales are not resident in the Auckland Islands throughout the season. The rarity of right whales along the main islands of New Zealand and their apparent increase in numbers in the Auckland Islands suggests a major shift in habitat use from pre-exploitation times or the loss of a component of a historically sub-divided stock.